2019
DOI: 10.1111/ped.13833
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of infant and maternal anemia during the lactation period in Japan

Abstract: Background The perinatal period is associated with a high risk of infant anemia. The aim of the present study was to determine the prevalence of infant and maternal anemia during the late lactation period and the risk factors for anemia in Japan. Methods This retrospective cohort study was based on data from health checkups of healthy infants at 6–7 and 9–10 months of age and their mothers who visited Akitsu Children's Clinic between September 2013 and August 2015. Complete blood count data from infant blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 51 publications
2
21
1
1
Order By: Relevance
“…An extensive study examining Filipino infant and child feeding (6–23 months of age) in urban areas reported that children who are breastfed were more likely to be anaemic or iron deficient after 6 months of age than those receiving fortified foods [ 7 ]. This is similar to results reported in other countries including India, China and Japan [ 22 24 ]. Fortified young child beverages provide a source of iron among Filipino infants (6–11.9mo) and toddlers (12–23.9mo), respectively [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…An extensive study examining Filipino infant and child feeding (6–23 months of age) in urban areas reported that children who are breastfed were more likely to be anaemic or iron deficient after 6 months of age than those receiving fortified foods [ 7 ]. This is similar to results reported in other countries including India, China and Japan [ 22 24 ]. Fortified young child beverages provide a source of iron among Filipino infants (6–11.9mo) and toddlers (12–23.9mo), respectively [ 5 ].…”
Section: Discussionsupporting
confidence: 92%
“…An extensive study examining Filipino infant and child feeding (6-23 months of age) in urban areas reported that children who are breastfed were more likely to be anaemic or iron de cient after 6 months of age than those receiving forti ed foods [7]. This is similar to results reported in other countries including India, China and Japan [22][23][24]. Forti ed young child beverages provide a source of iron among Filipino infants (6-11.9mo) and toddlers (12-23.9mo), respectively [5].…”
Section: Discussionsupporting
confidence: 77%
“…A domestic survey of nutritional conditions in China in 2013 showed that infants aged 5 months to 1 year had the highest prevalence rate of IDA, with the IDA prevalence rate in male infants 38.3% and that in female infants being 34.7% [ 1 ]. In 2019, a study in Japan reported by Amano et al showed that male infants were more likely to develop IDA than female infants [ 15 ]. However, in 2019, in Iran, Riahi et al reported no statistically significant difference in the prevalence of IDA between male and female infants [ 16 ].…”
Section: Discussionmentioning
confidence: 99%